Rapid Detection of SARS-CoV-2 Using Duplex Reverse Transcription-Multienzyme Isothermal Rapid Amplification in a Point-of-Care Testing - Chen, Hui; Sun, Chang; Wang, Yang; Gao, Xiaojiao; You, Jinwei; Yu, Wanwan; Sun, Ning; Yang, Yang; Li, Xiaojun (Frontiers in Cellular and Infection Microbiology, 2021)
In December 2019, a severe acute respiratory syndrome caused by SARS-CoV-2 spread rapidly worldwide. Portable nucleic acid tests of SARS-CoV-2 is critically important for diagnostics. In this study, we used an isothermal amplification method-Multienzyme Isothermal Rapid Amplification (MIRA) for rapid detection of SARS-CoV-2. We designed the primers and probes in ORF1ab and N gene of SARS-CoV-2. The amplicons could be monitored by lateral flow dipsticks (LFDs). The reaction temperature, time, concentrations of primers and probes and working volume were optimized. Four commercially swab collection buffers were used to test amplification efficacy of our assay without RNA extraction. Our assay was able to amplify duplex targets of SARS-CoV-2 in one single reaction using one-step RT-MIRA. The assay worked well in a low volume of 3.1μl at 38℃ for 20min. Using three collection buffers without guanidinium, our assay was able to amplify efficaciously without RNA extraction. The limit of detection (LoD) of the RT-MIRA assay was 50 copies per ml. There is no cross reaction with other human respiratory pathogens, such as influenza A virus, influenza B virus, human adenovirus, respiratory syncytial virus, human parainfluenza virus and coronavirus 229E in our assay. This assay also showed high anti-interference ability. The extraction-free RT-MIRA and qPCR detection results of 243 nucleic acid specimens from suspected patients or national references showed a 100% positive agreement value and a 100% negative agreement value. Compared with qPCR, the kappa value of the two assays was 1.00 (P < 0.0001). In conclusion, we provide a portable and visualized method for detection of SARS-CoV-2 without RNA extraction, allowing its application in SARS-CoV-2 on-site detection.